Impact of monitoring and training on biomedical waste segregation practice in hospitals - Mondal, Ramkrishna (International Journal Of Community Medicine And Public Health, 2022)
Background: It is evident that only 10-20% of the entire hospital waste is hazardous. If waste segregation is done properly at point of generation and immediately, it helps to reduce the waste quantity by around 2-5%. Regular monitoring and training of the staff is of paramount importance in proper segregation of waste. The aim was to find out impact of monitoring and training in waste segregation practice of the hospital. Methods: The study was done in a 750 bedded teaching hospital at eastern India during 2018. 23 different areas were identified. Each area had equipped with total five (5) bins including one bin for general waste and a total 23×5=115 bins to be monitored daily for segregation deficiency. A structured training programme for all staff were made. A register used to record daily segregation deficiency. Monthly data were used for training need assessment and bio-medical waste segregation deficiency (BMWSD) index was calculated. Simple statistical test in Microsoft excel and t test used. Results: In the zero month 16 areas found with total 38 deficiencies and the mean BMWSD index was 1.10%. On the third month, only three deficiencies found in three areas with the mean BMWSD index 0.09%. On the sixth month the deficiencies were further reduced to only one area with one deficiency with a BMWSD index of 0.03%. Conclusions: Regular monitoring along with proper training of the staff improved the biomedical waste segregation practice in the hospital highly significantly over time (p<0.0001).